Climate change and its implications for central banks in emerging and developing economies - Arndt, Channing; Loewald, Christopher; Makrelov, Konstantin (South African Reserve Bank, 2020)
Climate change mitigation and adaptation will prove to be sources of significant structural change. The impacts will be far-reaching and often irreversible, with particularly large effects on emerging and developing economies. This paper assesses the implications of these changes for central banks in developing countries. They can best support adaptation and mitigation efforts by maintaining macroeconomic stability, lowering the cost of borrowing to support green investment, facilitating the development of green assets, and improving the sharing of information in the financial system, especially with respect to risks. Yet, emerging market central banks currently have limited capacity to assess climate risks and their effects on financial stability, growth, and inflation. As such, the paper also provides options for central banks to develop analytical frameworks useful for that purpose.